2016
DOI: 10.1161/circep.116.004272
|View full text |Cite
|
Sign up to set email alerts
|

Macroreentrant Loop in Ventricular Tachycardia From the Left Posterior Fascicle

Abstract: Background— The underlying mechanisms of reentry during left posterior fascicular ventricular tachycardia (LPF-VT) remain unclear. The purpose of this study is to describe the components of LPF-VT reentry circuit and their electrophysiological properties. Methods and Results— Fourteen consecutive patients with LPF-VT underwent electrophysiology study and radiofrequency ablation. Via a multipolar electrode catheter placed from a retrograde aortic approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 14 publications
1
23
2
Order By: Relevance
“…Recently, there have been a number of reports on so-called “Purkinje-related arrhythmias,” including F-VT 1, 3. Although P1 is the common target of catheter ablation for F-VT, P1 cannot be recorded in up to one third of cases using linear catheters 4 . There may be some anatomical limitations in such cases: P1 fiber may not be long or parallel to the long axis of the LV, which makes it difficult to record P1 with linear catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been a number of reports on so-called “Purkinje-related arrhythmias,” including F-VT 1, 3. Although P1 is the common target of catheter ablation for F-VT, P1 cannot be recorded in up to one third of cases using linear catheters 4 . There may be some anatomical limitations in such cases: P1 fiber may not be long or parallel to the long axis of the LV, which makes it difficult to record P1 with linear catheters.…”
Section: Discussionmentioning
confidence: 99%
“…found that the sharp retrograde Purkinje potential (PP) following the local ventricular ECG could be recorded at the left posterior fascicular region during normal sinus rhythm in patients with LPF-ILVT. [ 25 ] They also demonstrated that the retrograde PP during normal sinus rhythm correlated with the diastolic PP during tachycardia. Ablation at the retrograde PP sites rendered tachycardia non-inducible ( Figure 7 ).…”
Section: Mapping and Ablationmentioning
confidence: 98%
“…Ouyang et al speculated that the reentrant circuit of LPF-ILVT may consist of antegrade and retrograde Purkinje potentials, bridged by ventricular myocardium. [ 24 ] Recently, further investigation of the mechanism of LPF-ILVT was reported by Liu et al[ 25 ] In that study, multipolar electrode catheters were used to continuously record the P1 and P2 potentials. Both the P1 and P2 potentials could be recorded in 64% of patients, which is consistent with the findings of Nogami’s study.…”
Section: Re-entry As the Mechanism Of Purkinje-related Idiopathic Lefmentioning
confidence: 99%
“…First, the timing of the earliest ventricular activation at the anteroseptum in parallel with the onset of QRS does not support a diagnosis of ILVT or the participation of the NF fiber with a breakthrough remote from the basal ventricle as the antegrade conductive pathway during the pre‐excited tachycardia. Furthermore, this does not exclude the participation of the NV fiber (Figure ) …”
Section: Commentarymentioning
confidence: 99%